1982
DOI: 10.1002/1097-0142(19820301)49:5<1016::aid-cncr2820490527>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

The American Burkitt's lymphoma registry:Eight years' experience

Abstract: Four-hundred-twenty-one Americans diagnosed as having Burkitt's lymphoma (BL), 409 from the United States, were studied by the American BL Registry to obtain information about the cause and control of this disease. Of these 421 cases, 256 were confirmed by our pathologists as being morphologically indistinguishable from African BL, A relationship between age and organ involvement was observed; cervical lymph nodes, ileum, and nasopharynx were initial sites of involvement primarily in younger patients. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
5

Year Published

1982
1982
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(64 citation statements)
references
References 23 publications
5
54
0
5
Order By: Relevance
“…3,9 In our patients, the positive correlation between sex ratio and age class was the same as the lower proportion of young males in high risk (endemic) areas. Interestingly, the opposite is not the case in the USA or the Middle East, 9,15 indicating that global sex ratio estimates in endemic and sporadic areas do not represent the extremes of a single distribution. This reinforces the need to carry out genetic and environmental studies per age class to search for biological factors involved in age-specific risk in BL.…”
Section: Demographic Characteristicsmentioning
confidence: 97%
“…3,9 In our patients, the positive correlation between sex ratio and age class was the same as the lower proportion of young males in high risk (endemic) areas. Interestingly, the opposite is not the case in the USA or the Middle East, 9,15 indicating that global sex ratio estimates in endemic and sporadic areas do not represent the extremes of a single distribution. This reinforces the need to carry out genetic and environmental studies per age class to search for biological factors involved in age-specific risk in BL.…”
Section: Demographic Characteristicsmentioning
confidence: 97%
“…Knowles and Jakobic in their review of 60 patients with orbital lymphoid neoplasm reported that the most common physical finding was a palpable mass in 90% of cases and proptosis is in 33%, like the presented case 15 . Central nervous system disease has been reported by Levine et al as one of the most common sites for BL, with 5% of involvement and therefore a high suspicious must be maintained when patients presents with orbital signs 18 . Some cases could present systemic spread in sporadic BL but in the presented case the patient didn`t have it.…”
Section: Discussionmentioning
confidence: 99%
“…Cytologically identical tumor has been sporadically found also in patients of a non-African origin most often located in the gastrointestinal tract, ovaries and kidneys. The difference between the nonAfrican and the African type is the less frequent osseous tumors and the more frequent affection of nasopharynx and terminal ileum (Levine et al, 1982). Burkitt's lymphoma usually is encountered with in young people and is the most frequent type of the juvenile NHL (Gisselbrecht et al, 1998).…”
Section: Burkitt's Lymphoma/diffuse Small Noncleaved Cell Lymphomamentioning
confidence: 99%
“…In cases of impossibility for resection or spreadout disease: combined chemiotherapy is optional, irradiation is used to inhibit the rysk of reoccurrance. In some cases marrow transplantation is performed (Levine et al, 1982).…”
Section: Burkitt's Lymphoma/diffuse Small Noncleaved Cell Lymphomamentioning
confidence: 99%